Mixing Chromophores: Donor–Acceptor Dyes with Low‐Lying LUMOs and Narrow Band Gaps by Connecting 4‐Alkoxythiazoles and Azaacenes. Issue 10 (15th March 2017) - Gampe, Dominique Mario; Hänsch, Veit Georg; Schramm, Stefan; Menzel, Roberto; Weiß, Dieter; Beckert, Rainer
Abstract : The synthesis and characterization of novel donor–acceptor (D–A) type functional dyes is presented. The materials studied are based on the 4‐alkoxythiazole structure containing one of three arylamine donor units and one of three acceptor building blocks. The nine dyes were characterized with respect to their photo‐ and electrochemical properties based on UV/Vis absorption and fluorescence emission spectroscopy, as well as cyclic voltammetry. Density functional theory calculations were carried out to support these investigations. The building blocks used brought their characteristics into the final target structures: the reversible oxidation and electron‐donating properties of diarylamines, the high fluorescence quantum yields of 4‐alkoxythiazoles, and the low‐lying LUMOs of tetraazaanthracenes. Furthermore, by introducing tetraazaanthracenes as the acceptor moiety, very narrow band gaps of 1.1 and 0.7 eV were estimated electrochemically. Abstract : The synthesis and characterization of donor–acceptor (D–A) type dyes is described. The "mixture" of three arylamine donor moieties with three electron acceptors around the 4‐alkoxythiazole scaffold affords nine molecules with a wide range of features. For the first time, tetraazaanthracene is used as an electron‐withdrawing building block; this leads to low LUMO levels and very narrow band gaps.